Disseminating and Hiding Information in Technical Communication Courses: The Case of Patents from the Perspectives of Digital Humanities - Anesa, Patrizia; Arina Pellón, Ismael (HERMES - Journal of Language and Communication in Business, 2019)
Despite their ostensibly aseptic nature, technical texts involve a multifaceted net of institutional, social and pragmatic functions. Patents, in particular, are characterized by a multi-layered rhetorical exercise in which information is provided, and hidden, in light of patent disclosure lawsDrawing on the Cooperative Patent Classification scheme, a corpus of patents related to environmental issues has been compiled. The objective is to investigate the main keywords emerging in the corpus and to analyse their semantic context in this patent type. More specifically, the analysis focuses on the patents’ semantic preference and semantic prosody in order to pinpoint and examine the semantic complexities emerging in this genre and to identify the strategies employed (such as the use of linguistic vagueness) in order to provide the necessary information while not disclosing precious data. Patents represent a complex, hybrid and cross-disciplinary genre and a finer understanding of their discursive features may contribute to spreading awareness of the importance that semantics plays within the rhetorical pattern of the text. Therefore, they may be fruitfully employed in Technical Communication courses in order to improved reading comprehension and analytical skills.